(untitled) (Nexo Revista Científica, 2023)
Cement pastes were prepared on a laboratory scale, varying the % of CCA and the % of lime (90-10, 80-20 and 70-30), the % of Na2O used as alkaline activator (6, 8 and 10%) and the setting temperature (80, 90 and 100 ºC). A total of 9 pastes were prepared, obtaining significant compressive strength results at 28 days of curing. The optimal mixture was made with 90% CCA - 10% lime, activated with 10% Na2O in the form of sodium silicate and set at 100 ºC for 24 hours. From the analysis of variance it was deduced that the % of CCA and % of lime is the variable that mainly affects the values of compressive strength obtained. By infrared spectroscopy it was confirmed that the alkaline activation with sodium silicate had an effect on the three-dimensional network of SiO2 of the CCA, generating different reaction products to the starting raw material.